Terapi Cuci Hidung Dengan Nacl Dapat Meningkatkan Sensitivitas Penciuman Pada Pasien Penyintas Covid-19: Therapy With NaCl Can Increase Olfactory Sensitivity in Covid-19 - Rizki Putra Pamungkas, Muhamad (Dohara POAJ, 2022)
Introduction: Covid-19 is an infectious disease caused by a newly discovered type of coronavirus. COVID-19 is transmitted during respiratory contacts such as coughing and vomiting. One form of its clinical manifestations interferes with the respiratory system. The process begins with the occurrence of olfactory and taste dysfunction. For example, mechanical blockages that prevent odor from reaching the olfactory nerve can lead to a loss of sense of smell. Washing your nose with NaCl fluid is one of the things that is recommended when infected with COVID-19. Washing the nose is useful to reduce symptoms of anosmia or loss of sense of smell. Methods: This type of research is using quantitative research, with queasy research experimentation through the One Group Pretest and Posttest Design approach, Sampling techniques using Random sampling which is as many as 17 respondents. The study measure used a smelling instrument of 3 items and each item was rated by the patient from 1 to 10 to assess the patient's impaired life. Results: Test statistics using the Wilcoxon test. The result of a significant level of olfactory sensitivity with a value p-value of 0.000 which means p-value <0.05, therefore Ho was rejected and Ha was accepted. Discussion: That there is an effect of giving nasal washing therapy with NaCl to the level of olfactory sensitivity in patients who survive covid 19.